2021
DOI: 10.3389/fmed.2021.774644
|View full text |Cite
|
Sign up to set email alerts
|

Veno-Arterial Extracorporeal Membrane Oxygenation for Patients Undergoing Heart Transplantation: A 7-Year Experience

Abstract: Objective: Primary graft dysfunction (PGD) is the leading cause of early death after heart transplantation. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) can provide temporary mechanical circulatory support and time for functional recovery of the transplanted heart. The purpose of this study was to analyze the timing and prognoses of VA-ECMO in patients with severe PGD after heart transplantation.Methods: A total of 130 patients underwent heart transplantation at the Zhongshan Hospital Affiliated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…VA-ECMO can also be used in cardiac arrest through extracorporeal cardiopulmonary resuscitation (ECPR), as well as in cases where temporary mechanical support is needed as a bridge prior to left ventricular assist device (LVAD) placement or cardiac transplant [2,4]. It has been reported that VA-ECMO can be an effective treatment for ventricular septal rupture and severe primary graft dysfunction after cardiac transplantation [35][36][37][38]. In addition, there have been case reports describing the use of VA-ECMO in the management of COVID-19-associated acute myocardial injury complicated by cardiogenic shock, though additional studies are needed in order to accurately assess its safety and in this subset of patients [39,40].…”
Section: Indications and Contraindications Of Va-ecmomentioning
confidence: 99%
“…VA-ECMO can also be used in cardiac arrest through extracorporeal cardiopulmonary resuscitation (ECPR), as well as in cases where temporary mechanical support is needed as a bridge prior to left ventricular assist device (LVAD) placement or cardiac transplant [2,4]. It has been reported that VA-ECMO can be an effective treatment for ventricular septal rupture and severe primary graft dysfunction after cardiac transplantation [35][36][37][38]. In addition, there have been case reports describing the use of VA-ECMO in the management of COVID-19-associated acute myocardial injury complicated by cardiogenic shock, though additional studies are needed in order to accurately assess its safety and in this subset of patients [39,40].…”
Section: Indications and Contraindications Of Va-ecmomentioning
confidence: 99%
“…Therefore, the Research Topic of indications, procedures, management, and even transport of ECMO patients will never be out of date.In this Research Topic, we were able to collect volume II of advances in extracorporeal life support in critically ill patients (https://www.frontiersin.org/research-topics/33279/advancesin-extracorporeal-life-support-in-critically-ill-patients-volume-ii). The topic comprises 17 papers in this Research Topic, of which 12 are original researches and five are case reports, encompassing indications, procedure, management and complications of extracorporeal life support.As a salvage therapy, ECMO can be life-saving in numerous clinical scenarios (5,6). In this volume, Xu et al reported a case of a 14-year-old adolescent male patient with an anomalous left coronary artery originating from the right coronary sinus rescued by VA-ECMO and Intra-Aortic Balloon Pump followed.…”
mentioning
confidence: 99%
“…As a salvage therapy, ECMO can be life-saving in numerous clinical scenarios ( 5 , 6 ). In this volume, Xu et al reported a case of a 14-year-old adolescent male patient with an anomalous left coronary artery originating from the right coronary sinus rescued by VA-ECMO and Intra-Aortic Balloon Pump followed.…”
mentioning
confidence: 99%